Regulation of autophagy and lipid accumulation under phosphate limitation in Rhodotorula toruloides - Wang, Ya-nan; Liu, Fang-jie; Liu, Hong-di; Zhang, Yue; Jiao, Xiang; Ye, Ming-liang; Zhao, Zong-bao Kent; Zhang, Su-fang (Frontiers in Microbiology, 2023)
Background It is known that autophagy is essential for cell survival under stress conditions. Inorganic phosphate (Pi) is an essential nutrient for cell growth and Pi-limitation can trigger autophagy and lipid accumulation in oleaginous yeasts, yet protein (de)-phosphorylation and related signaling events in response to Pi limitation and the molecular basis linking Pi-limitation to autophagy and lipid accumulation remain elusive. Results Here, we compared the proteome and phosphoproteome of Rhodotorula toruloides CGMCC 2.1389 under Pi-limitation and Pi-repletion. In total, proteome analysis identified 3,556 proteins and the phosphoproteome analysis identified 1,649 phosphoproteins contained 5,659 phosphosites including 4,499 pSer, 978 pThr, and 182 pTyr. We found Pi-starvation-induced autophagy was regulated by autophagy-related proteins, but not the PHO pathway. When ATG9 was knocked down, the engineered strains produced significantly less lipids under Pi-limitation, suggesting that autophagy required Atg9 in R. toruloides and that was conducive to lipid accumulation. Conclusion Our results provide new insights into autophagy regulation under Pi-limitation and lipid accumulation in oleaginous yeast, which should be valuable to guide further mechanistic study of oleaginicity and genetic engineering for advanced lipid producing cell factory.